Climate change related litigation in Indonesia - Linda Yanti Sulistiawati (Communications Earth & Environment, 2024)
Abstract Indonesia contributes to greenhouse gas emissions but is also vulnerable to climate change. However, the country does not have a single, overarching law explicitly addressing climate change. Climate litigation is now used in Indonesia to hold governments and corporations accountable. Here, I review the courts’ decisions for criminal and civil climate change-related cases between 2010 and 2020 and highlight trends and examples of case studies, driving factors, and impacts of climate litigation cases in Indonesia. I show that 112 climate change-related cases were brought to Indonesian courts, most of which were criminal cases concerning forestry or forest fires. In addition, there were a number of civil court cases. The cases use phrases concerning climate change in their main claim, argument, evidence, expert witness arguments, and judgments. They are regarded as incidental climate change litigation cases. However, these cases are essential in developing climate change litigation in Indonesia because they open up a discussion of climate change issues in the Indonesian courts and public media.